Separation of Anions on Polar Stationary Phases in Hydrophilic Interaction Liquid Chromatography - Mayaserli, Dyna Putri; Zein, Rahmiana; Refilda, Refilda; Putra, Adewirli; Toyohide Takeuchi (JURNAL KATALISATOR, 2024)
The need for the detection of anions and cations in various environmental water samples more rapidly with increasing environmental problems and the time it takes the proper method of analysis, is fast, simple, and can provide an accurate assessment. Hydrophilic Interaction Liquid Chromatography (HILIC) is a highly precise technique for separating polar compounds or hydrophilic compounds. Various places have been making a lot of market columns and columns designed specifically for HILIC. For that to be done selection of the appropriate column to separate compounds primarily for separating anions using polar aminopropyl silica stationary phases, HILIC imidazole, pyridine, and Polar Amide-80. Polar stationary phases are best to separate the anions are aminopropyl silica (NH2-60) because it can separate the anions without adding salt. While Polar pyridine can separate anions at low pH (4.2) using acidic stationary phases and at low pH Polar pyridine can serve as an ion exchanger (ion exchange) Keywords: polar stationary phase, HILIC, ion exchange chromatography